2021
DOI: 10.1186/s12905-021-01360-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of obstetrics fistula patients before and after surgical repair in the Jimma University Medical Center, Southwest Ethiopia

Abstract: Background The consequences of obstetric fistula on affected women are more than the medical condition. It has extensive physical, psychological, social, and economic consequences on them. Obstetric fistula affects the entire health and entire life of women. Women suffering from obstetric fistula are often abandoned by her partner, relatives, and the community. This study aimed to determine the quality of life of obstetrics fistula patients before and after surgical repair. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…As a result, their self-con dence and self-esteem were improved, survivors were reunited with their families, and most could take part again in the social activities. Studies in Africa also revealed similar ndings (4,(10)(11)(12)14). In Kenya for instance, following the project implementation, there was an increased self-esteem and involvement of women in decision making on matters that involved their health and wellbeing in general (12).…”
Section: Discussionmentioning
confidence: 66%
“…As a result, their self-con dence and self-esteem were improved, survivors were reunited with their families, and most could take part again in the social activities. Studies in Africa also revealed similar ndings (4,(10)(11)(12)14). In Kenya for instance, following the project implementation, there was an increased self-esteem and involvement of women in decision making on matters that involved their health and wellbeing in general (12).…”
Section: Discussionmentioning
confidence: 66%
“…Surgical repair shows improvement in quality-of-life scores, including overall satisfaction, psychological health domains, and bladder and sexual function, and helps women regain a place within their communities. 26,43,60,61 Although the old tenets of surgical repair yield high success rates, surgeons still have a responsibility to identify what is best practice. Beyond surgical repair, rehabilitation and reintegration programs are critical.…”
Section: Discussionmentioning
confidence: 99%
“…It is a public health issue for women and communities within developing countries, particularly in Africa and Southeast Asia. Obstetrics fistula which signifies a health system that has failed to provide accessible, timely, and appropriate intrapartum care, improving health care workers' knowledge, practices and attitudes regarding obstetric fistula could help in its prevention 4 Obstetric fistula is a public health concern for women and women's communities within developing nations, particularly in Africa and Southeast Asia and it is found to be one of the most visible indicators of maternal morbidity 7 The current study aimed to assess Pregnant Women`s knowledge and attitude Regarding Obstetric Fistula. The findings of the current study will be discussed under four main sections, characteristic of the studied women, knowledge of the studied women regarding obstetric fistula, attitude of the studied women regarding obstetric fistula, and the final section reflected relation between level of total knowledge, attitude score and socio-demographic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“… Part (2): obstetrical history which consisted of (7) items such as( age of marriage, age at first child, the number of pregnancies, history of abortion, previous birth method, the place where the previous child was born and had obstetric fistula before).…”
Section: Samplingmentioning
confidence: 99%